Ethnic Minority Analysts’ Participation in Public Earnings Conference Calls - FLAM, RACHEL W.; GREEN, JEREMIAH; LEE, JOSHUA A.; SHARP, NATHAN Y. (Journal of Accounting Research, 2023)
ABSTRACT We investigate ethnic minority and nonminority sell‐side analysts’ participation in public earnings conference calls. We find that minority analysts are underrepresented in conference call Q&A sessions, and minority analysts who do participate on the calls experience lower levels of prioritization than do nonminority analysts. Minority analysts’ lower participation rates are partially but not fully mediated by characteristics such as experience, work environment, and stock rating favorability. Additionally, firm and conference call fixed effects mediate approximately half the magnitude of lower minority participation rates. Extroverted minority analysts participate at higher rates, but the negative association between minority status and conference call participation is exacerbated when calls are more time constrained, when executive teams are less diverse, and when analysts are from less prestigious brokerage houses. Overall, we document the underrepresentation of minority analysts on earnings conference calls and provide evidence suggesting both analysts’ and managers’ choices influence minority analysts’ participation rates.